2020
DOI: 10.1111/ijfs.14606
|View full text |Cite
|
Sign up to set email alerts
|

Dietary whole Goji berry (Lycium barbarum) intake improves colonic barrier function by altering gut microbiota composition in mice

Abstract: Diet strongly affects human health by modulating gut microbiota (GM) composition. Lycium barbarum (LB), which contains polysaccharides and polyphenols, can alter the GM and intestinal barrier function, thereby reducing and preventing the occurrence of intestinal diseases. To investigate how LB improves colonic barrier function, male C57BL/6J mice were fed diets containing 1.5% or 3% LB for 10 weeks. Results of HiSeq 16S rDNA analysis showed that LB markedly altered microbial profile by supporting the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…PrevotellaceaeUCG_001 is related to polysaccharide degradation and SCFA production (Heinritz et al ., 2016). SCFAs produced by gut microbiota play an important role to rectify metabolism and immunity (Tian et al ., 2020). These results showed that MBO consumption could increase the abundance of some benign bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…PrevotellaceaeUCG_001 is related to polysaccharide degradation and SCFA production (Heinritz et al ., 2016). SCFAs produced by gut microbiota play an important role to rectify metabolism and immunity (Tian et al ., 2020). These results showed that MBO consumption could increase the abundance of some benign bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…As a naturally occurring chemical, LBP is the water-soluble glycoconjugates with a molecular weight from 10-2300 kDa [15]. Due to their various pharmacological effects, including anti-oxidation, anti-aging, immune regulation, improvement of gut microbiota and reproductive protection [16][17][18][19][20][21], LBP has been widely exploited in healthy foods and medicine in China. Although the comprehensive pharmacological studies of LBP have been performed, there is still only limited information on the pharmacokinetics and excretion study of this compound in vivo given their high molecular size.…”
Section: Introductionmentioning
confidence: 99%
“…Goji ( Lycium barbarum ) belongs to the Solanaceae family and its berry (also called wolfberry) is a well‐known traditional Chinese herbal medicine and valuable tonic food for centuries (Xie et al, 2016; Zhang et al., 2016). Medical research has evidenced their potential impact on human health, such as improving visual acuity, reducing blood sugar levels, decreasing the risk of cancer and cell senescence, improves colonic barrier function and improving immunity (Huang et al., 2019; Tian et al., 2020; Yao et al., 2018). Recently, further studies have been conducted to identify the bioactive ingredients of goji fruits and clarify their bioactivities.…”
Section: Introductionmentioning
confidence: 99%